Effect of SO2 content on SCC behavior of E690 high-strength steel in SO2-polluted marine atmosphere. (15th September 2018) - Ma, Hongchi; Du, Cuiwei; Liu, Zhiyong; Li, Xiaogang
Abstract: Slow strain rate tensile (SSRT) test in a simulated device was employed to investigate the effect of SO2 on stress corrosion cracking (SCC) behavior of E690 steel in SO2 -polluted marine atmosphere. Results revealed that SO2 can greatly enhance the SCC susceptibility of E690 steel in marine atmosphere and the SCC mechanism in this environment is a combination of anodic dissolution (AD) and hydrogen embrittlement (HE). The increase of SCC susceptibility was attributed to the formation of a compact rust layer on steel surface that SCC microcracks can initiate from the bottom of cracks in the rust layer consequently. Moreover, hydrogen evolution was greatly enhanced with the increase of SO2 content, and SCC susceptibility increased rapidly as a result. Highlights: A device was set up to investigate the SCC behavior in simulated marine atmosphere containing SO2 . Effect of SO2 content on SCC behaviors of E690 steel was investigated and its affecting mechanism was illustrated. The role of corrosion products scale with SO2 on SCC initiation was revealed.